Construction Industry–Associated Penetrating Craniocerebral Injuries - Su, Jiahao; Liang, Sitao; Lin, Qichang; Hu, Zihui; Liao, Wei; Zhu, Yonghua (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Various high-energy tasks in the construction industry can lead to craniocerebral injuries. Construction industry–associated penetrating craniocerebral injuries due to metal foreign bodies have unique characteristics. However, no norms exist for removing metal foreign bodies and preventing secondary trauma. This study aimed to explore the characteristics and treatment of construction industry–associated penetrating craniocerebral injuries due to metal foreign bodies.Methods Data of patients who suffered from penetrating injuries due to metal foreign bodies and were treated in the Zhongshan People's Hospital from 2001 to 2021 were collected based on the causes of injuries to explore disease characteristics and therapeutic effects.Results A total of six patients with penetrating craniocerebral injuries due to metal foreign bodies, who underwent surgeries, were included in the study. Five patients recovered well after the surgery, and one patient died. In four patients, intracranial infection complicated the course after surgery, and two patients had delayed intracranial hematoma.Conclusion Patients with construction industry–associated penetrating craniocerebral injuries due to metal foreign bodies are prone to coma and intracranial vascular injuries. Early surgical removal and prevention of intracranial infection are key to achieving good therapeutic effects.
Keywords: craniocerebral injury; intracranial infection; metal foreign body